Assessing head and neck cancer patient preferences and expectations: A systematic review. (November 2016) - Blanchard, Pierre; Volk, Robert J.; Ringash, Jolie; Peterson, Susan K.; Hutcheson, Katherine A.; Frank, Steven J.
Highlights: First systematic review evaluating head and neck cancer patients' preferences. Patients prioritized survival over functional endpoints. A subset of patients is willing to compromise survival to avoid laryngectomy. Studies on oropharyngeal cancer (OPC) don't allow to draw functional trade-offs. Priorities of OPC patients should be the focus of future research. Abstract: Introduction: To enhance the value of care, interventions should aim at improving endpoints that matter to patients. The preferences of head and neck cancer patients regarding treatment outcomes are therefore a major topic for patient-centered research. Methods: A systematic review (PROSPERO number CRD42016035692) was conducted by searching electronic databases (Medline, Embase, Cochrane, CINAHL) for articles evaluating patient or surrogate preferences in head and neck cancer. A qualitative review was performed but no quantitative synthesis. Results: Of 817 references retrieved, 20 full-text articles were eventually included in the qualitative analysis Disease sites included mixed head and neck tumor sites, n = 9; larynx, n = 6; oropharynx/oral cavity, n = 5. Overall, patients prioritized survival over functional endpoints. However, preferences and utility scores varied greatly between patients and healthy subjects, and differences were less pronounced with spouses or healthcare providers. Findings from studies of laryngeal preservation are consistent and conclude that a subset of patients would be willing to compromise a certain amount of survival to avoid laryngectomy. On the other hand, studies of patients with oropharyngeal cancer are too heterogeneous to draw conclusions about acceptable functional trade-offs or priorities, and should be the focus of future research. Conclusion: Future research surrounding head and neck cancer patients will most likely be clinically applicable if the questions are focused on well-defined patient groups and treatment options. Gathering reliable and valid quality-of-life data, designing patient preference studies that use reliable and generalizable methods, and using the results to develop decision aids for shared decision-making strategies are recommended going forward.